2015
DOI: 10.7314/apjcp.2014.15.24.10705
|View full text |Cite
|
Sign up to set email alerts
|

Oral and IV Dosages of Doxorubicin-Methotrexate loaded-Nanoparticles Inhibit Progression of Oral Cancer by Down-Regulation of Matrix Methaloproteinase 2 Expression in Vivo

Abstract: Asian Pac J Cancer Prev, 15 (24), 10705-10711 IntroductionSquamous cell carcinomas encompass approximately 95% of all oral malignancies. Oral cancer holds the sixth position in cancer incidence ranking worldwide (Albano et al., 2013;Baykara et al., 2013). Squamous cell carcinoma (SSC) of the tongue has historically been shown to be associated with a poor prognosis , much more an aggressive biological and clinical behavior and a high metastatic potential (Jones et al., 1992; BrandweinGensler et al., 2005;Kadema… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
28
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 31 publications
(28 citation statements)
references
References 38 publications
0
28
0
Order By: Relevance
“…We have clearly demonstrated the importance of cortisol on oral cancer cells' ability to survive and combat the effectiveness of two (Abbasi et al, 2014). However, the current study is the first to investigate and demonstrate the effect of DOXO in vitro on several human OSCC cell lines, indicating its future potential for the treatment of OSCC.…”
Section: Discussionmentioning
confidence: 78%
“…We have clearly demonstrated the importance of cortisol on oral cancer cells' ability to survive and combat the effectiveness of two (Abbasi et al, 2014). However, the current study is the first to investigate and demonstrate the effect of DOXO in vitro on several human OSCC cell lines, indicating its future potential for the treatment of OSCC.…”
Section: Discussionmentioning
confidence: 78%
“…In addition, UA inhibited the ability of Ca922 cells to invade Matrigel‐coated membranes in a concentration‐dependent manner (Figure C). Previous studies reported that the overexpression of matrix metalloproteinase (MMP)‐2 is associated with the regional relapse of OSCC, and its downregulation inhibited OSCC progression in a chemotherapeutic agent‐treated animal model . We assessed if UA suppressed MMP‐2 activity in the conditioned medium using gelatin zymography.…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies reported that the overexpression of matrix metalloproteinase (MMP)-2 is associated with the regional relapse of OSCC, and its downregulation inhibited OSCC progression in a chemotherapeutic agent-treated animal model. 30,31 We assessed if UA suppressed MMP-2 activity in the conditioned medium using gelatin zymography. As shown in Figure 3D, the proteolytic activity of MMP-2 was reduced after UA treatment for 36 hours.…”
Section: In Addition Ua Inhibited the Ability Of Ca922 Cells To Invadementioning
confidence: 99%
“…Apoptosis and DNA damage was significantly increased in the dual-drug-loaded liposome group compared to other controls. Abbasi et al [53][54][55] examined stimuli-responsive cationic mesoporous silica NPs loaded with MTX and Dox on a 4-NQO-induced oral cavity SCC rat model. Both free and nanoforms of Dox combined with MTX were orally or IV administrated for 14 weeks.…”
Section: Doxorubicinmentioning
confidence: 99%